Analysis of heat transfer characteristics through an rectangular enclosure. (2021) - Saha, Sandip; Biswas, Pankaj; Narayan Das, Apurba; Raut, Santanu
Abstract: The aim of this present work is to investigate the characteristics of laminar airflow and heat transfer phenomena in a two-dimensional rectangular enclosure with isothermally heated baffles and adiabatic walls. Using the Boussinesq approximation and negligible viscous dissipation effect, the governing equations are solved using the finite volume method and fluent software is used to visualize the simulation results. Different forms of the baffles (trapezoidal, plane, and isosceles shapes) have been examined for several values of Reynolds number (Re) and Richardson number (Ri). In the form of isotherms, streamlines, heating efficiency, average bulk temperature, local and average Nusselt number along the hot surface, the results have been presented. Maximum heating efficiency is found to be achieved for higher values of Reynolds number, and Richardson number. In addition, it is noted that the efficiency of heat transfer decreases with the increase of baffle length. From this study, it is ensured that heat transfer enhancement becomes maximum in presence of plane baffles as compared to the other baffles.